Perancangan Sistem Informasi Evaluasi dan Latihan Agent Berbasis Web pada Perusahaan Business Process Outsourcing - Chicha Silvi Aulia; Purnomo Sidiq; Riska Endang Permata (Masoem University, 2026)
The use of information technology plays an important role in improving organizational efficiency, particularly in Business Process Outsourcing (BPO) companies that rely on Agent performance. This study aims to design a web-based Agent Evaluation and Training Information System to overcome the limitations of the existing system in quiz management, assessment, and reporting. The study applies the System Development Life Cycle (SDLC) using the Waterfall model and adopts the Object-Oriented Analysis and Design (OOAD) approach with Unified Modeling Language (UML). The proposed design identifies three main actors, namely Admin, Reviewer, and Agent, and includes modules for quiz management, evaluation, and reporting. Compared with the existing system, the proposed design provides campaign- or division-based question bank management, role-based evaluation mechanisms, and integrated reporting. The proposed design is expected to support a more flexible, accurate, and integrated Agent evaluation and training process.